2008
DOI: 10.1080/14767050801928804
|View full text |Cite
|
Sign up to set email alerts
|

An increased risk for non allo-immunization related intrauterine fetal death in RhD-negative patients

Abstract: RhD-negative women carrying RhD-positive newborns are at an increased risk for IUFD despite Rh immunoprophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Among the high risk Bedouin population of Beersheva Israel, Rh negative women experienced more stillbirths, even after receiving Anti-D [ 18 ] but miscarriage rates had not been analyzed. Our data describes a healthier population than that of Beersheva and found identical first trimester miscarriage rates for every blood type.…”
Section: Discussionmentioning
confidence: 99%
“…Among the high risk Bedouin population of Beersheva Israel, Rh negative women experienced more stillbirths, even after receiving Anti-D [ 18 ] but miscarriage rates had not been analyzed. Our data describes a healthier population than that of Beersheva and found identical first trimester miscarriage rates for every blood type.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Surprisingly no case of Rh isoimmunization were reported in our study, this is incontrase to the study done by Gila Ben-David a (2008)), he found that RhD-negative women carrying RhD-positive new-borns are at an increased risk for IUFD despite immunoprophylaxis. [30] A past history of intrauterine fetal death indicates some subclinical genetic or chromosomal problem which can reoccur in future pregnancies. In our study history of previous IUFD was seen in 43%.…”
Section: Discussionmentioning
confidence: 99%